Orang Tua Melek Teknologi Pembelajaran (Dampak Positif Pembelajaran Daring Bagi Orang Tua Siswa MIS Al-Quba Medan) - Irwanto, Irwanto; Habib, Abdul; Adawiyah, Rabiatul (Prodi PAI STAI Sumatera Medan, 2021)
This study aims to analyze the positive impact of online learning for parents, with three focus studies, namely parents' perceptions of online learning, the abilities and constraints of parents using the application. The research was conducted at MIS Al-Quba Medan in February-October 2021. This study used a case study-based qualitative method. Collecting data using observation, interview, and documentation techniques. Then analyzed with the stages of data reduction, data presentation, and drawing conclusions. The results showed that parents experienced a change in attitude from previously refusing online learning to accepting online learning. Regarding the perception that some parents consider online learning to be effective, they are more concerned with the safety of their children. However, some think it is not effective, because time and class management cannot be ascertained, so it is not possible to achieve learning objectives. Regarding ability, there are 53.33% of parents who are able to use both Google Classroom and Zoom applications, and 20% of parents are only able to use one of them, and 36.67 are unable to use both. The inability to use online learning applications is generally influenced by two factors, namely the attitude and competence.